Cover Jurnal Fitopatologi Vol. 19 No. 6, November 2023: Cover Jurnal Fitopatologi Vol. 19 No. 6, November 2023 - Editors Jurnal Fitopatologi Indonesia (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2023)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Vol. 19 No. 6, November 2023